Les conversions à l’islam en Asie mineure, dans les Balkans et dans le monde musulman (École française d’Athènes, 2022)
Research on how conversions to Islam were perceived in the historical literature of the 19th and 20th centuries resulted in the publication of an annotated bibliography in 2011 as part of the Mondes méditerranéens et balkaniques series of the French School at Athens (MMB 3). Continuing the ongoing discussion of the Seljuk and Ottoman eras in Asia Minor and the Balkans, eleven historians and humanities specialists, participants in a 2012 conference, consider conversion to Islam from a range of different perspectives, in different periods. The articles in this collection reconsider the Asia Minor and Balkan contexts and look at other cultures and time periods, such as the beginnings of Islam, Syria during the 17th-19th centuries, the Indian peninsula, and the Insulindian archipelago, while also paying attention to processes specific to Jewish groups (Marranos, Moriscos and Dönme-s).